Patterns and correlates of mental disability in euthymic patients with bipolar affective disorder: A descriptive study - Avinash D Karde; Smita N Panse; Manjit Santre (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Background: Substantial proportion of bipolar affective disorder (BPAD) patients are symptomatic more than half of their lives despite receiving pharmacological treatment leading to functional impairment and disability. Objectives: To study the correlation of disability with socio-demographic and clinical variables in euthymic patients with BPAD. Methods: A hospital-based cross-sectional study was conducted on 100 euthymic patients of BPAD using purposive sampling. Data were collected using semi-structured proforma and diagnostic categorization of patients was done according to ICD-10 research criteria, Hamilton's Rating Scale for Depression (HAM-D), and Young Mania Rating Scale (YMRS). Indian Disability Evaluation Assessment Scale (IDEAS) was administered for disability assessment. The variables were analyzed using appropriate tests, namely, analysis of variance (ANOVA) test, two independent sample t test, Fisher's exact test, and Spearman's correlation coefficient. Results: 81% patients of BPAD had a mild disability and 19% patients had a moderate disability. The total duration of illness score (mean 3.8) was the major determinant of disability on IDEAS. There was a statistically significant association of age (P < 0.001), gender (P = 0.027), subsyndromal manic features (P < 0.001), and number of previous episodes (P < 0.001) with disability, and there was no association of socioeconomic status, marital status, occupational status, duration of illness, age of onset, and number of previous hospitalizations with disability. Conclusion: Bipolar affective disorder is associated with mild-to-moderate disability on evaluation using IDEAS instrument. There is a need for further studies on the utility of IDEAS and its individual domains in the assessment of disability due to bipolar affective disorder.